Apoptosis, Necrosis, and Necroptosis in the Gut and Intestinal Homeostasis - Anna Negroni; Salvatore Cucchiara; Laura Stronati (Hindawi Limited, 2015)
Intestinal epithelial cells (IECs) form a physiochemical barrier that separates the intestinal lumen from the host's internal milieu and is critical for electrolyte passage, nutrient absorption, and interaction with commensal microbiota. Moreover, IECs are strongly involved in the intestinal mucosal inflammatory response as well as in mucosal innate and adaptive immune responses. Cell death in the intestinal barrier is finely controlled, since alterations may lead to severe disorders, including inflammatory diseases. The emerging picture indicates that intestinal epithelial cell death is strictly related to the maintenance of tissue homeostasis. This review is focused on previous reports on different forms of cell death in intestinal epithelium.